A city-level analysis of the distribution of FDI within China. Issue 1 (6th February 2017) - Cheng, Suwina; Lin, Kenny; Simmons, Richard
Abstract : Purpose: The study aims to examine whether city-level investment climate, local government effectiveness and corporate income tax rates influence the spatial distribution of foreign direct investment (FDI) across cities in China. Design/methodology/approach: The study uses regression analysis using city-level data sets. Findings: The study finds that while city-level investment climate and effective local government influence the spatial distribution of FDI across Chinese cities, city-level tax rates have no such influence. Practical implications: The results have implications for the design of policies aimed at enhancing FDI flows into emerging countries. Originality/value: To date, few studies have investigated the investment location choice at the city level in a single country. The study contributes to the literature by examining the role of government in such investment decisions. It also adds to the previously limited research examining the role of investment climate at the micro level.